Applicative Constructions in Belitong Language: A Morphosyntactic Study - I Nyoman Pasek Darmawan; Vindi Kaldina (Universitas Cokroaminoto Palopo, 2022)
This is a morphosyntactic study that analyses and describes applicative constructions in the Belitong language under the qualitative descriptive study alongside Relational Grammar (RG) theory. This study has suggested an extended version of the Belitong morphosyntactic phenomenon that accounted for the phenomenon of valency-raising constructions, applicative. The data were taken using the elicitation technique, interview with the native speakers, and documentation of the previous studies as well as some additional works of literature. Subsequently, the data were analyzed and scrutinized by following six procedural steps of the technique of analyzing qualitative data. The results of this study suggested that: (1) Belitong accounts for two types of applicative, normal and abnormal applicative constructions; (2) Both applicative constructions are marked naturally by suffixes -ek, -kan, -an, -rek, or zero marker -Ø right on the predicates; Applicative constructions are considered dealing with the revaluation, promotion, and demotion, as the analysis of arguments interchange from initial stratum to final stratum. Therefore, it can be concluded that the revaluation principles for normal applicative constructions are formulated as OBL–2 (intransitive); OBL–2, 2–Cho (transitive); and the abnormal applicative constructions such as OBL–1, 1–2 (intransitive); OBL–1, 1–2, 2–Cho (transitive).